Clinical outcomes of asleep vs awake deep brain stimulation for Parkinson disease. (7th November 2017) - Brodsky, Matthew A.; Anderson, Shannon; Murchison, Charles; Seier, Mara; Wilhelm, Jennifer; Vederman, Aaron; Burchiel, Kim J.
Abstract : Objective: To compare motor and nonmotor outcomes at 6 months of asleep deep brain stimulation (DBS) for Parkinson disease (PD) using intraoperative imaging guidance to confirm electrode placement vs awake DBS using microelectrode recording to confirm electrode placement. Methods: DBS candidates with PD referred to Oregon Health & Science University underwent asleep DBS with imaging guidance. Six-month outcomes were compared to those of patients who previously underwent awake DBS by the same surgeon and center. Assessments included an "off"-levodopa Unified Parkinson's Disease Rating Scale (UPDRS) II and III, the 39-item Parkinson's Disease Questionnaire, motor diaries, and speech fluency. Results: Thirty participants underwent asleep DBS and 39 underwent awake DBS. No difference was observed in improvement of UPDRS III (+14.8 ± 8.9 vs +17.6 ± 12.3 points, p = 0.19) or UPDRS II (+9.3 ± 2.7 vs +7.4 ± 5.8 points, p = 0.16). Improvement in "on" time without dyskinesia was superior in asleep DBS (+6.4 ± 3.0 h/d vs +1.7 ± 1.2 h/d, p = 0.002). Quality of life scores improved in both groups (+18.8 ± 9.4 in awake, +8.9 ± 11.5 in asleep). Improvement in summary index ( p = 0.004) and subscores for cognition ( p = 0.011) and communication ( p < 0.001) were superior in asleep DBS. Speech outcomes were superior in asleep DBS, both in category (+2.77 ± 4.3 points vs −6.31 ± 9.7 points ( p = 0.0012) and phonemic fluency (+1.0 ± 8.2 points vs −5.5 ± 9.6 points, p = 0.038). Conclusions: Asleep DBS for PD improved motor outcomes over 6 months on par with or better than awake DBS, was superior with regard to speech fluency and quality of life, and should be an option considered for all patients who are candidates for this treatment. Clinicaltrials.gov identifier: NCT01703598. Classification of evidence: This study provides Class III evidence that for patients with PD undergoing DBS, asleep intraoperative CT imaging–guided implantation is not significantly different from awake microelectrode recording–guided implantation in improving motor outcomes at 6 months.